Smoking behaviors, intentions and beliefs among dublin primary-school children - Crube, Joel W.; Morgan, Mark; Mcgree, Sheila (Economic & Social Studies, 1984)
Abstract: Cigarette smoking and related beliefs were investigated in a survey of 752 Dublin sixth class primary school children. Smoking rates and differences in the beliefs and background of smokers and non-smokers are described. The relative importances of different beliefs as predictors of future smoking intentions also were ascertained. For both boys and girls the most important predictors of intentions were perceived peer smoking and evaluation of negative consequences of smoking. Parental smoking also was important for boys and parental disapproval and perceived likelihood of negative consequences were important for girls. The implications for smoking interventions among young people are discussed.
Keywords: Cigarettes; School Children